- Marital differences and their impact on raising children - Contemporary study - Yusuf, Bara‘ah Ali (Journal of Humanities & Social Sciences, 2018)
God created and blessed Adam and peace be upon him and created his wife to live in it and make love and mercy between them. He said: "And from His Signs is that He created for you wives from among yourselves، to dwell in them and to make between you affection and mercy. And to be God’s successors in the land. If the love and compassion between them were lost، the family collapsed. This resulted in many psychological، social and moral problems that affect the family، including the children. From this point of view I went to discuss the real meaning of the marital differences and their impact on the family in general، and on the education of children and their behavior in particular، and the implications of those differences on the Islamic community.